Mycoprotein ingredient structure reduces lipolysis and binds bile salts during simulated gastrointestinal digestion. Issue 12 (26th November 2020) - Colosimo, Raffaele; Mulet-Cabero, Ana-Isabel; Warren, Frederick J.; Edwards, Cathrina H.; Finnigan, Tim J. A.; Wilde, Pete J.
Abstract : Mycoprotein is an ingredient used in meat replacement products that reduces lipolysis and binds bile salts during simulated gastrointestinal digestion. Abstract : Mycoprotein is the fungal biomass obtained by the fermentation of Fusarium venenatum, whose intake has been shown to lower blood lipid levels. This in vitro study aimed to understand the mechanisms whereby mycoprotein can influence lipid digestion by reducing lipolysis and binding to bile salts. Mycoprotein at 30 mg mL −1 concentration significantly reduced lipolysis after 60 min of simulated intestinal digestion with oil-in-water emulsion ( P < 0.001) or 10 min of incubation with tributyrin ( P < 0.01). Furthermore, mycoprotein effectively bound bile salts during simulated small intestinal digestion, but only after being exposed to the acidic environment of the preceding gastric phase. However, the extent of bile salts sequestered by mycoprotein was decreased by pepsin and lipase–colipase activity. Besides, extracted mycoprotein proteins showed bile salt binding activity, and proteins with a molecular weight of ∼37 kDa showed resistance to trypsin hydrolysis. Thus, eleven extracted mycoprotein proteins (> 37 kDa) were identified by liquid chromatography-tandem mass spectrometry. In addition, the viscosity of mycoprotein digesta appeared to have no impact on bile salt binding since no statistically significant differences were detected between samples exposed or not to the previous gastric step. This study has identified mechanisms by which mycoprotein can reduce blood lipid levels.